Factors determining profitability of banks in UAE. (23rd September 2019) - Chotia, Varun; Pai, Rajesh Jayakar
The objective of this study is to examine and evaluate the micro- and macro-factors that affect the profitability of the banks operating on the domestic outskirts of UAE during the post-crisis period. An analysis is done to evaluate the relationship between the financial ratios of a few of the local banks in the UAE using the data of the past nine years, i.e. 2009 to 2017 (the post-crisis period). The study show the results that the factor most adversely impacting the profitability in banks like Abu Dhabi Commercial Bank, Commercial Bank of Dubai, Dubai Islamic Bank and Emirates Islamic Bank, is 'interest income' whereas that in banks like Emirates National Bank of Dubai, Mashreq Bank, United Arab Bank and United National Bank, is 'wages' as per cent of the total expenses.